The Accuracy of Newspaper Citation Count Reported and Actual Citation Found in Web of Science Citation Database - Ravikumar; Warjri, Sweety (Journal of Information and Knowledge, 2018)
Bibliometric indicators are widely used in evaluating research output. Citation information about a publication can be obtained from various databases like Web of Science (WoS), SCOPUS and Google Scholar. Bibliometricans solely depend on the above databases to get citation data. WoS is considered a credible source for citation data. In this paper, we have tried to study the accuracy of the citation count reported and actually found with special reference to three newspapers namely Wall Street Journal, Washington Post, and Guardian. It was found that only 69% of citation data was accurate for above three newspapers.